Exclusive breastfeeding and smoking behavior as determinants of ARI in toddlers - Wijaya, Dian Rezki; Wulandari, Tri; Nildawati (CORE JOURNAL, 2023)
Acute Respiratory Infections (ARI) are one of the leading causes of childhood morbidity and mortality worldwide, with ARI accounting for one-third of under-five deaths in low-income countries. One of the factors that influence the incidence of ARI in toddlers is the exclusive breastfeeding and smoking behavior of parents of toddlers and in the neighborhood. This study aims to determine the relationship between exclusive breastfeeding and smoking behavior with the incidence of ARI in toddlers in the working area of the Turikale Health Center, Maros Regency. This study used a type of quantitative research with a cross-sectional study design, with a population of 120 toddlers. Sampling was done using accidental sampling. The results showed that the variables of exclusive breastfeeding (p-value = 0.003) and smoking behavior (p-value = 0.000) were associated with the incidence of ARI in toddlers in the Turikale Puskesmas Working Area, Maros Regency. It is expected for health workers to increase counseling related to exclusive breastfeeding and parents to keep toddlers away from smokers so they are not exposed to cigarette smoke